Symmetrical Musical Structures in the Credo From Missa Popularis (Mårten Jansson) - Ana-Maria MELINTE (Studia Universitatis Babeş-Bolyai. Musica)
Missa popularis, was premiered on 25 April 2015, and is a fascinating interplay between simplicity and depth, between musical creation and sacred text. Our analysis is limited to the vocal performance system, trying to grasp the relationship between the text and melos, based on the premise proposed by Jansson himself that music is an expression of his Christian faith and a form of respect and genuine humility before the sacred text, a wonderful “offering” given to God, personally, through the act of composing, and ecclesiastically, through the act of performing. As he often stated about himself, Mårten Jansson is a ‘homo religiosus’, being rather a searcher for “beautiful music”, which could match the timeless sacred texts, than a composer stricto sensu.